Response and resilience of Asian agrifood systems to COVID-19: An assessment across twenty-five countries and four regional farming and food systems. (October 2021) - Dixon, John M.; Weerahewa, Jeevika; Hellin, Jon; Rola-Rubzen, Maria Fay; Huang, Jikun; Kumar, Shalander; Das, Anup; Qureshi, Muhammad Ejaz; Krupnik, Timothy J.; Shideed, Kamil; Jat, Mangi L.; Prasad, P.V. Vara; et al.
Abstract: Context: The COVID-19 pandemic has been affecting health and economies across the world, although the nature of direct and indirect effects on Asian agrifood systems and food security has not yet been well understood. Objectives: This paper assesses the initial responses of major farming and food systems to COVID-19 in 25 Asian countries, and considers the implications for resilience, food and nutrition security and recovery policies by the governments. Methods: A conceptual systems model was specified including key pathways linking the direct and indirect effects of COVID-19 to the resilience and performance of the four principal Asian farming and food systems, viz, lowland rice based; irrigated wheat based; hill mixed; and dryland mixed systems. Based on this framework, a systematic survey of 2504 key informants (4% policy makers, 6% researchers or University staff, 6% extension workers, 65% farmers, and 19% others) in 20 Asian countries was conducted and the results assessed and analysed. Results and conclusion: The principal Asian farming and food systems were moderately resilient to COVID-19, reinforced by government policies in many countries that prioritized food availability and affordability. Rural livelihoods and food security were affected primarily because of disruptions to local labour markets (especially for off-farm work), farm produce markets (notably for perishable foods) and input supply chains (i.e., seeds and fertilisers). The overall effects on system performance were most severe in the irrigated wheat based system and least severe in the hill mixed system, associated in the latter case with greater resilience and diversification and less dependence on external inputs and long market chains. Farming and food systems' resilience and sustainability are critical considerations for recovery policies and programmes, especially in relation to economic performance that initially recovered more slowly than productivity, natural resources status and social capital. Overall, the resilience of Asian farming and food systems was strong because of inherent systems characteristics reinforced by public policies that prioritized staple food production and distribution as well as complementary welfare programmes. With the substantial risks to plant- and animal-sourced food supplies from future zoonoses and the institutional vulnerabilities revealed by COVID-19, efforts to improve resilience should be central to recovery programmes. Significance: This study was the first Asia-wide systems assessment of the effects of COVID-19 on agriculture and food systems, differentiating the effects of the pandemic across the four principal regional farming and food systems in the region. Graphical abstract: Notes: Full lines denote direct effects; dashed lines indirect effects; and thickness of line denotes relative strength of effects. Unlabelled Image Highlights: This regional synthesis addresses a major gap in knowledge about the effects of COVID-19 on agriculture and food across Asia Key informants from 20 Asian countries assessed early direct and indirect effects on each of four major regional farming and food systems The analysis showed Asian farming and food systems were moderately resilient to the pandemic, especially the hill mixed system System resilience, food and labour markets, and farm and food chain economic benefits are key priorities for recovery policies and programmes This study highlights COVID-19 effects and informs recovery policies and precautionary strategies against future pandemics in Asia and globally